Enhanced Hemodynamic and Clinical Response to αCGRP in Migraine Patients—A TCD Study - Visočnik, Darja; Zaletel, Marjan; Žvan, Bojana; Zupan, Matija (Frontiers in Neurology, 2021)
Introduction: Sensitisation of the nervous system in a patient with migraine is supposed to be associated with calcitonin gene-related peptide (CGRP) activity. Therefore, the vascular response to human αCGRP (hαCGRP) could be a surrogate marker for the sensitization. We hypothesize that vascular response to hαCGRP is augmented in a patient with migraine. Methods: Twenty healthy subjects and 20 patients with migraine participated in our study. TCD was used to monitor mean arterial velocity in the middle cerebral artery (vm MCA). Simultaneously, end-tidal CO2 (Et-CO2), mean arterial pressure (MAP), and heart rate (HR) were measured. The reconstruction of the signals was made for basal conditions, during and after CGRP infusion which were compared using statistics. Results: In both groups, we found significant decrease between measurement points of vm MCA and Et-CO2 during and after hαCGRP infusion. MAP did not show significant trends during the infusion, but it was significantly increased after the infusion in migraine patients only. Responses to hαCGRP, defined as differences between two measurement points, were significantly higher for vm MCA and Et-CO2 in patients with migraine. A significant difference between groups was found in MAP response. Significant relationships were found between migraine and vm MCA, Et-CO2, and MAP. Conclusion: In patients with migraine, vm MCA responses to hαCGRP are significantly higher and are associated with CGRP-induced headache which indicates that patients with migraine are more prone to sensitization.